Information frictions, internet and the relationship between distance and trade - Anders Akerman; Edwin Leuven; Magne Mogstad (University of Oslo, Department of Economics, 2017)
Recent work suggests the patterns of international trade may be distorted because of information frictions. Little is known, however, about how advancements in information communication technology (ICT) affect trade patterns. The goal of our paper is to analyze how and why the adoption of such technology affects bilateral trade flows. Our context is the adoption of broadband internet in Norwegian firms over the period 2000-2008. We use panel data with information on Norwegian firms with regards to their production, technology, and trade. A public program with limited funding rolled out broadband access points, and provides plausibly exogenous variation in the availability and adoption of broadband internet in firms. We find that adoption of broadband internet makes trade patterns more sensitive to distance and economic size. Going from no broadband availability to full coverage increases the magnitude of the elasticity of trade with respect to distance by 0.12, and the elasticity of trade with respect to destination size by 0.06. For distance, this means that an increase in internet availability of 10 percentage points increases trade for a country at the 25th distance percentile by 1.1% more than for a country at the 75th distance percentile. The same difference for the GDP of a destination is 2.1%. We interpret the empirical results through a gravity theory of trade patterns, augmented with information frictions. We provide comparative statics predictions with respect to a reduction in information frictions, and show that these predictions are consistent with our empirical findings. Taken together, our results point to the importance of incorporating information frictions in the frequently used gravity equation, and they may help explain the so-called "distance puzzle" in international trade.
Keywords: F12; F15; F61; O33; 330; Internet; Trade; Information Frictions; Gravity model; Distance